2010
DOI: 10.1271/bbb.90535
|View full text |Cite
|
Sign up to set email alerts
|

Culm in Rice Straw as a New Source for Sugar RecoveryviaEnzymatic Saccharification

Abstract: Rice straw was manually dissected and two main fractions were recovered: a culm and a leaf sheath/blade fraction, in order to evaluate their potential as feedstocks for the recovery of fermentable sugars. In the case of cv. Koshihikari and Milkyqueen, most soft carbohydrates (SCs: glucose, fructose, sucrose, starch, and beta-1,3-1,4-glucan) were present in the culms, reaching 47.9% and 89.2% of total SCs in the two main fractions. The results also indicated that beta-glucans (cellulose and beta-1,3-1,4-glucan)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Meanwhile, recent analyses of the carbohydrate components of rice straw demonstrated that this feedstock possesses a remarkable advantage over other agricultural wastes in that it often contains so-called soft carbohydrates (SCs: glucose, fructose, sucrose, starch and b-1,3-1,4-glucan), as well as cellulose and xylan (Park et al, 2009(Park et al, , 2010a(Park et al, , 2010bShiroma et al, 2011). In some cases, the amounts of SCs in rice straw are larger than the cellulose content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, recent analyses of the carbohydrate components of rice straw demonstrated that this feedstock possesses a remarkable advantage over other agricultural wastes in that it often contains so-called soft carbohydrates (SCs: glucose, fructose, sucrose, starch and b-1,3-1,4-glucan), as well as cellulose and xylan (Park et al, 2009(Park et al, , 2010a(Park et al, , 2010bShiroma et al, 2011). In some cases, the amounts of SCs in rice straw are larger than the cellulose content.…”
Section: Introductionmentioning
confidence: 99%
“…Harsh pretreatment for cell walls could over degrade some SCs (mainly fructose residues or reducing sugars, depending on the chemicals and heat conditions) (Park et al, 2010a). In addition, solid-liquid separation processes after some pretreatments, which are often used for pH neutralization and reagent recovery/ removal, would remove some SCs after the pretreatments (Park et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…1) Bioethanol is considered an important alternative to gasoline for transportation, because it can reduce the emission of CO 2 which contributes to the global greenhouse effect. 2) To address global warming and safeguard global energy issues, it is alluring to produce bioethanol from lignocellulosic biomass to avoid competition between food and fuel production.…”
mentioning
confidence: 99%
“…17) In the case of cultivars Koshihikari and Milkyqueen, most of the SCs including starches at the mature stage were present in the culms, reaching 47.9% and 89.2% of the total SCs in the straw. 18) Together with the results indicating that -glucans and xylans in the culms are more susceptible to enzymatic attack, culms show high potential as a feedstock for the extraction of fermentable sugars. 18) Hence we focused on the culms as a source of starch.…”
mentioning
confidence: 82%
“…18) Together with the results indicating that -glucans and xylans in the culms are more susceptible to enzymatic attack, culms show high potential as a feedstock for the extraction of fermentable sugars. 18) Hence we focused on the culms as a source of starch.…”
mentioning
confidence: 82%